Attention fine-tunes auditory-motor processing of speech sounds - Möttönen, Riikka; van de Ven, G.M.; Watkins, K.E. (Society for Neuroscience, 2014)
The earliest stages of cortical processing of speech sounds take place in the auditory cortex. Transcranial magnetic stimulation (TMS) studies have provided evidence that the human articulatory motor cortex contributes also to speech processing. For example, stimulation of the motor lip representation influences specifically discrimination of lip-articulated speech sounds. However, the timing of the neural mechanisms underlying these articulator-specific motor contributions to speech processing is unknown. Furthermore, it is unclear whether they depend on attention. Here, we used magnetoencephalography and TMS to investigate the effect of attention on specificity and timing of interactions between the auditory and motor cortex during processing of speech sounds. We found that TMS-induced disruption of the motor lip representation modulated specifically the early auditory-cortex responses to lip-articulated speech sounds when they were attended. These articulator-specific modulations were left-lateralized and remarkably early, occurring 60–100 ms after sound onset. When speech sounds were ignored, the effect of this motor disruption on auditory-cortex responses was nonspecific and bilateral, and it started later, 170 ms after sound onset. The findings indicate that articulatory motor cortex can contribute to auditory processing of speech sounds even in the absence of behavioral tasks and when the sounds are not in the focus of attention. Importantly, the findings also show that attention can selectively facilitate the interaction of the auditory cortex with specific articulator representations during speech processing.